Proceedings of the 2018 EMNLP Workshop SCAI: The 2nd International Workshop on Search-Oriented Conversational AI 2018
DOI: 10.18653/v1/w18-5704
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Evaluating Interaction Strategies of Task-Oriented Conversational Agents

Abstract: In task-oriented conversational agents, more attention has been usually devoted to assessing task effectiveness, rather than to how the task is achieved. However, conversational agents are moving towards more complex and human-like interaction capabilities (e.g. the ability to use a formal/informal register, to show an empathetic behavior), for which standard evaluation methodologies may not suffice. In this paper, we provide a novel methodology to assess-in a completely controlled way-the impact on the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…formal vs. informal register) as used in goal-oriented settings by Joshi et al (2017); Luo et al (2019) to provide personalized interactions. Further, Guerini et al (2018) showed how injecting these specific persona-related aspects into a conversation can positively affect the interaction in goal-oriented scenarios, both in terms of quality of service and overall perceived quality.…”
Section: Related Workmentioning
confidence: 99%
“…formal vs. informal register) as used in goal-oriented settings by Joshi et al (2017); Luo et al (2019) to provide personalized interactions. Further, Guerini et al (2018) showed how injecting these specific persona-related aspects into a conversation can positively affect the interaction in goal-oriented scenarios, both in terms of quality of service and overall perceived quality.…”
Section: Related Workmentioning
confidence: 99%